(untitled) (MASKAY, 2019)
This study aimed to optimize irrigation water in the potato (Solanum tuberosum L. cv INIAP Natividad) crop to ensure the maximum productivity of the crop, using WSN according to the agro-ecological conditions of the area, which has allowed the monitoring of environmental parameters in potato cultivation and have ensured an efficient control system in irrigation. The WSN irrigation network was implemented using four Arduino modules configured with 6LoWPAN; two modules controlled the solenoid valves with FC-28 sensors, which capture soil moisture and, through the DHT11 sensor, the temperature and relative humidity. The fourth module functioned as a gateway through which information is sent to a database developed in PostgreSQL. Additionally, a web server (Apache) was configured to visualize the control of the drip irrigation system developed in PHP and JAVA. It was concluded that the T1 (automated irrigation) had achieved evidence of a higher productivity in potato cultivation of 19.2%, with a water consumption of 20% less than the T2 (manual irrigation). This evidences a clear saving of the hydric resource and an optimum potato crop development compared to traditional irrigation systems.